Antiinflammatory Efficacy of Extracts of Latex of Calotropis procera Against Different Mediators of Inflammation. Issue 4 (2005) - Arya Arya, Soneera Soneera; Kumar Kumar, Vijay L. Vijay L.
Abstract : The latex of the plant Calotropis procera has been reported to exhibit potent antiinflammatory activity against carrageenin and formalin that are known to release various mediators. In the present study, we have evaluated the efficacy of extracts prepared from the latex of C procera against inflammation induced by histamine, serotonin, compound 48/80, bradykinin (BK), and prostaglandin E 2 (PGE 2 ) in the rat paw oedema model. The paw oedema was induced by the subplantar injection of various inflammagens and oedema volume was recorded using a plethysmometer. The aqueous and methanol extracts of the dried latex (DL) and standard antiinflammatory drugs were administered orally 1 hour before inducing inflammation. The inhibitory effect of the extracts was also evaluated against cellular influx induced by carrageenin. The antiinflammatory effect of aqueous and methanolic extracts of DL was more pronounced than phenylbutazone (PBZ) against carrageenin while it was comparable to chlorpheniramine and PBZ against histamine and PGE 2, respectively. Both extracts produced about 80%, 40%, and 30% inhibition of inflammation induced by BK, compound 48/80, and serotonin. The histological analysis revealed that the extracts were more potent than PBZ in inhibiting cellular infiltration and subcutaneous oedema induced by carrageenin. The extracts of DL exert their antiinflammatory effects mainly by inhibiting histamine and BK and partly by inhibiting PGE 2 .